Oxidative Stress and Nutritional Antioxidants in Renal Diseases: A Narrative Review - Dorin Dragoș; Iulia I. Enache; Maria M. Manea (Antioxidants)
Oxidative stress is a key component in the pathogenesis of a broad number of renal disorders, including acute kidney injury, chronic kidney disease, and various types of nephropathies. Moreover, oxidative stress seems to at least partly explain the intricate relationship the kidney has with other pathological entities, for instance with cardiovascular comorbidities. Renal replacement therapies give end-stage renal disease patients a fighting chance; however, even these interventions may carry the risk of enhancing existing oxidative stress. Even if nutritional components are not currently routinely used, many have shown promise in preclinical or even clinical studies and could counter some of the deleterious pathways that oxidative stress sets in place. This narrative review provides an update on how these natural nutrients could be beneficial to renal disease patients, and it also aims to give an incentive to future research in the field.